Understanding the roles of the healthcare and child welfare systems in promoting the safety and well-being of children - Joh-Carnella, Nicolette; Livingston, Eliza; Kagan-Cassidy, Miya; Vandermorris, Ashley; Smith, Jennifer N.; Lindberg, Daniel M.; Fallon, Barbara (Frontiers in Psychiatry, 2023)
Abstract Introduction: The accurate identification and appropriate investigation of child maltreatment is a key priority for promoting the optimal health and development of children. Healthcare providers are often well-positioned professionals to report suspected child abuse and neglect, and, therefore, interact regularly with child welfare workers. Little research has examined the relationship between these two groups of professionals. Methods: We interviewed healthcare providers and child welfare workers in order to examine the referral and child welfare investigation processes to understand strengths and identify areas of improvement for future collaboration. Thirteen child welfare workers from child welfare agencies and eight healthcare providers from a pediatric tertiary care hospital in Ontario, Canada were interviewed to meet the study’s objectives. Results: Healthcare providers spoke about positive experiences making reports, factors impacting reporting decisions, areas for improvement (e.g., difficulties communicating, lack of collaboration, and disruption of therapeutic alliance), training, and professional roles. For interviews with child welfare workers, identified themes included healthcare professionals’ perceived expertise and understanding the role of child welfare. Both groups brought up the need for increased collaboration as well as systemic barriers and legacies of harm. Discussion: Our core finding was a reported lack of communication between the groups of professionals. Other identified barriers in collaboration included a lack of understanding of each other’s roles, hesitation for healthcare providers making reports, as well as legacies of harm and systemic inequities in both institutions. Future research should build on this examination by including the voices of healthcare providers and child welfare workers to identify sustainable solutions for increased collaboration.